2006
DOI: 10.1126/science.1123052
|View full text |Cite
|
Sign up to set email alerts
|

High Natural Aerosol Loading over Boreal Forests

Abstract: Aerosols play a key role in the radiation balance of the atmosphere. Here, we present evidence that the European boreal region is a substantial source of both aerosol mass and aerosol number. The investigation supplies a straightforward relation between emissions of monoterpenes and gas-to-particle formation over regions substantially lacking in anthropogenic aerosol sources. Our results show that the forest provides an aerosol population of 1000 to 2000 particles of climatically active sizes per cubic centime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
416
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 480 publications
(448 citation statements)
references
References 22 publications
30
416
2
Order By: Relevance
“…The direct contribution of anthropogenic emissions to SOA is small, but anthropogenic aerosols may serve as nuclei for biogenic SOA formation and growth 42 . Recent work has shown that monoterpenes are the chief determinant of aerosol mass over boreal forests 43 , and that sesquiterpene oxidation products are crucial for the initial stages of particle formation 44 . The situation with isoprene is more complex: it has been recognized as an SOA precursor 45,35 , but isoprene has also been shown to suppress particle formation from monoterpenes, probably through competing reactions with OH (ref.…”
Section: From Gases To Particlesmentioning
confidence: 99%
“…The direct contribution of anthropogenic emissions to SOA is small, but anthropogenic aerosols may serve as nuclei for biogenic SOA formation and growth 42 . Recent work has shown that monoterpenes are the chief determinant of aerosol mass over boreal forests 43 , and that sesquiterpene oxidation products are crucial for the initial stages of particle formation 44 . The situation with isoprene is more complex: it has been recognized as an SOA precursor 45,35 , but isoprene has also been shown to suppress particle formation from monoterpenes, probably through competing reactions with OH (ref.…”
Section: From Gases To Particlesmentioning
confidence: 99%
“…Subsequently, only the data relative to the four summer months from June to September were considered when calculating the long-term variations of AOD, with the background contribution hereafter referred to as BG, and enhancements attributed to extinction mainly by smoke particles from boreal forest fires (hereafter referred to as FFS) in North America and Siberia (Forster et al, 2001;Damoah et al, 2004;Stohl et al, 2006;Tunved et al, 2006). Following the same approach used by Tomasi et al (2007), this summer-time analysis ignores influences of AH and/or Asian dust (AD) that occur mainly during late winter and spring (Rahn et al, 1977;Shaw, 1982Shaw, , 1983VanCuren and Cahill, 2002;Stone et al, 2007;Quinn et al, 2007).…”
Section: Long-term Variations In Aerosol Optical Depth At Arctic Sitesmentioning
confidence: 99%
“…Fuentes et al, 2000) and serve as precursors for secondary organic aerosols (SOA) (Hallquist et al, 2009). In regions with low pre-existing particulate matter, VOC oxidation can produce low volatile products which are involved in new particle formation (Tunved et al, 2006). Emissions of isoprene and monoterpenes (MT) from vegetation are well known and their dependence on parameters such as light intensity and temperature can be described semi-empirically (Guenther, 2007).…”
Section: Introductionmentioning
confidence: 99%